2016
DOI: 10.2151/jmsj.2016-024
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Variation in Surface Shortwave Irradiance in China and Japan: A Review

Abstract: We reviewed the long-term trends and inter-annual variations in the surface shortwave irradiance in China and Japan. Pyranometer observations revealed decreases followed by increases in the shortwave irradiance in China and Japan between the 1960s and 2000s, while obvious long-term trends were not evident in the satellite observations after 1983. In China, surface shortwave irradiance decreased from 1961 until around 1990, but then began to increase. In Japan, on the contrary, the decreasing trend stopped in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 101 publications
(139 reference statements)
3
8
0
Order By: Relevance
“…The MRI‐AGCM simulates a 3.3 W/m 2 difference in shortwave radiation between the HPB and HPB NAT climates at the beginning of the study period (Figure (a)). We believe this difference in shortwave radiation between the HPB and HPB NAT simulations by the AGCM occur because of differences in the input anthropogenic aerosol and water vapor data, in agreement with Hayasaka (). Overall, the global anthropogenic effect on climate based on differences between 2001–2010 and 1951–1960 is as follows: a 4.07 ± 0.66‐W/m 2 decrease in mean shortwave radiation, a 1.20 ± 0.18 °C increase in temperature, a 28.66 ± 13.52‐mm/year increase in precipitation, a 0.89 ± 0.09‐hPa increase in vapor pressure, and a 0.01 ± 0.02‐m/s decrease in wind speed.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The MRI‐AGCM simulates a 3.3 W/m 2 difference in shortwave radiation between the HPB and HPB NAT climates at the beginning of the study period (Figure (a)). We believe this difference in shortwave radiation between the HPB and HPB NAT simulations by the AGCM occur because of differences in the input anthropogenic aerosol and water vapor data, in agreement with Hayasaka (). Overall, the global anthropogenic effect on climate based on differences between 2001–2010 and 1951–1960 is as follows: a 4.07 ± 0.66‐W/m 2 decrease in mean shortwave radiation, a 1.20 ± 0.18 °C increase in temperature, a 28.66 ± 13.52‐mm/year increase in precipitation, a 0.89 ± 0.09‐hPa increase in vapor pressure, and a 0.01 ± 0.02‐m/s decrease in wind speed.…”
Section: Resultssupporting
confidence: 83%
“…To the best of our knowledge, there is no observational evidence of a long‐term decrease in surface shortwave radiation with large decadal variability (Wild, ). Previous observation‐based studies have reported that surface shortwave radiation decreased until the 1980s and increased in many regions since then (Hayasaka, ). The MRI‐AGCM simulates a 3.3 W/m 2 difference in shortwave radiation between the HPB and HPB NAT climates at the beginning of the study period (Figure (a)).…”
Section: Resultsmentioning
confidence: 99%
“…5a, 6b), consistent with the "global dimming" scenario reported in Wild (2012). Hayasaka (2016) reports that the decreasing trend of the downward solar flux at the surface after the early-2000s exists in several regions especially in China and Japan, as well as in the tropics (Zhou et al 2016). Since the decadal upward SW flux change is negligible, the decrease of downward SW radiative flux at the surface also implies a decrease of surface SW absorption.…”
Section: Global Warming Hiatus Periodsupporting
confidence: 84%
“…Observational globalmean temperature trends also corroborate the important contribution of deep ocean heat uptake to the warming hiatus as the 1-100 m ocean layer has slightly cooled, while the 101-300 and 701-1500 m layers have warmed (Cheng et al 2015(Cheng et al , 2017. Additionally, the global brightening phase of the 1980s and 1990s transitions into a dimming phase in the 2000s in many regions of the world (Norris and Wild 2009;Hayasaka 2016;Wild 2012Wild , 2017, indicating there is a reduction of SW radiative flux received by the surface during the global warming hiatus period. Individual radiative contributions to the surface energy budget from feedback processes including snow and ice cover, water vapor, and ozone may be overwhelmed by contributions from cloud changes (Trenberth and Fasullo 2009).…”
Section: Introductionmentioning
confidence: 56%
“…The dimming and leveling-off phases were defined as the periods 1960-1989 and 1990-2013, respectively, according to the change point in the early 1990s in sunshine duration trends in China evidenced by previous studies (e.g., Xia, 2010;Wang et al, 2013;Hayasaka, 2016; Urbanization effect on trends in sunshine duration in China 841 2014). The year 1990 was also identified as the transition year for the surface solar radiation trend in China Tang et al, 2011;Wang and Wild, 2016).…”
Section: Methodsmentioning
confidence: 99%